Pengembangan Aplikasi Pelaporan Mentoring Universitas Teknologi Sumbawa Berbasis Web - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Ryan Suarantalla; Musthofa Luthfi Al Manfaluty (STMIK Budi Darma, 2021)
Mentoring is one of the activities that function to foster students in the religious field under the student activity unit, namely the Mentoring Unit. This mentoring activity is also one of the requirements for passing student evaluation activities. Reports that run in the Mentoring Unit are still manual or not yet computerized, such as in attendance, recitations, and exams. To overcome the problems that occurred above, a web based application development for mentoring from the University of Technology Sumbawa was made using the PHP programming language, Laravel framework and MySQL as a database. The software development method used is the waterfall and the Unified Modeling Language (UML) modeling method. The results of the mentoring reporting application can make it easier for the Mentoring Unit to report every week or period